2022
DOI: 10.3389/fphys.2022.889792
|View full text |Cite
|
Sign up to set email alerts
|

Roles of NRF2 in Fibrotic Diseases: From Mechanisms to Therapeutic Approaches

Abstract: Fibrosis is a persistent inflammatory response that causes scarring and tissue sclerosis by stimulating myofibroblasts to create significant quantities of extracellular matrix protein deposits in the tissue. Oxidative stress has also been linked to the development of fibrosis in several studies. The nuclear erythroid 2-related factor 2 (NRF2) transcription factor controls the expression of several detoxification and antioxidant genes. By binding to antioxidant response elements, NRF2 is activated by oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…Moreover, cells and tissues are damaged when the oxidative stress caused by ROS exceeds the body's defenses. 33 The results of this study demonstrated that severe oxidative stress to the liver of CRS rats inhibited Nrf2 nuclear transfer. In this study, brusatol could significantly reverse the protective effect of LYC, increase ROS levels and MDA content, and aggravate hepatic oxidative stress.…”
Section: ■ Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, cells and tissues are damaged when the oxidative stress caused by ROS exceeds the body's defenses. 33 The results of this study demonstrated that severe oxidative stress to the liver of CRS rats inhibited Nrf2 nuclear transfer. In this study, brusatol could significantly reverse the protective effect of LYC, increase ROS levels and MDA content, and aggravate hepatic oxidative stress.…”
Section: ■ Discussionmentioning
confidence: 62%
“…GSH, SOD, and CAT constitute the antioxidant defense system in organisms and play a key role in scavenging oxygen-free radicals and peroxides. Moreover, cells and tissues are damaged when the oxidative stress caused by ROS exceeds the body’s defenses . The results of this study demonstrated that severe oxidative stress to the liver of CRS rats inhibited Nrf2 nuclear transfer.…”
Section: Discussionmentioning
confidence: 66%
“…Although the antifibrotic effect of Nrf2 has been observed previously, it has been assumed that Nrf2 primarily suppresses oxidative stress via the expression of antioxidant genes such as GSTs, HO-1, and NQO1, and the consequent inhibition of ROS injury or signaling contributes to antifibrosis 47 . In contrast, we discovered that Nrf2 directly regulates the transcription of profibrotic genes independently of ROS scavenging, at least in the context of fibroblast activation.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, activated inflammatory cells produce ROS, which, in turn, recruit other inflammatory cells and amplifying the damage ( Nathan, 2003 ). Nuclear factor erythroid 2–related factor 2 (Nrf-2) is a master regulator of cellular resistance to oxidative stress via modulation of the expression of genes encoding antioxidant enzymes and genes controlling immune and inflammatory responses, tissue remodeling and fibrosis ( Hao et al, 2022 ). Alterations in the redox state activate Nrf2 which upregulates the production of antioxidant, xenobiotic-metabolizing, and cytoprotective enzymes, safeguarding cells against ROS ( Chan and Kan, 1999 ).…”
Section: Discussionmentioning
confidence: 99%